A Comparative Study on Feto-Maternal Outcome of GDM Treated by Either Insulin or Metformin (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Background: Gestational Diabetes Mellitus (GDM) is linked with amplified risk of variety of maternal and perinatal complications. There have been a number of studies comparing metformin with insulin in the management of GDM.Methods: A clinical trial (Quasi experimental) was conducted on fifty women with GDM at their 24 – 34 weeks of gestation with the aim to compare maternal and perinatal outcomes treated by either insulin or metformin. The study population were recruited from obstetrics and gynaecology outpatient department of Medical College for Women and Hospital, Uttara, Dhaka, from July 2012 to December 2012.The patients were divided into two groups (nonrandomized), 25 patients in each, and were subjected to either injection insulin or oral metformin medication.Results: The patients were grouped as insulin or metformin group. They were compared in terms of age, parity and developing maternal complications like preeclampsia (p=0.24), UTI (p=0.40), polyhydramnios (p=0.70). However, the incidence of preterm birth was higher among metformin group in comparison to insulin group (P=0.007).There was no significant difference between insulin and metformin group as regard to mode of delivery. The proportion of neonatal hypoglycemia in insulin group was higher than metformin group (P=0.46) but statistically not significant. Other neonatal outcomes such as macrosomia, birth asphyxia and hyperbillirubinaemia did not differ significantly between two groups.Conclusion: In women with GDM, treatment with metformin is associated with higher proportion of preterm birth than with insulin. Proportion of neonatal hypoglycemia is higher with insulin use.Bangladesh J Obstet Gynaecol, 2019; Vol. 34(1): 8-14